2009
DOI: 10.1007/s00203-009-0464-0
|View full text |Cite
|
Sign up to set email alerts
|

Exopolysaccharide from surface-liquid culture of Clonostachys rosea originates from autolysis of the biomass

Abstract: We describe the purification and chemical characterization of galactomannans that appear both in the biomass and the culture broth during surface-liquid culture of the fungus Clonostachys rosea, a common facultative saprophyte that has potential to be used as a biological control agent against several plant pathogenic fungi, insects and nematodes. The galactomannans from both sources had comparable ratios of Man, Gal and Glc and the similarity were confirmed by (1)H, (13)C NMR, HMQC, and COSY spectra. We propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Examination of the 2D NMR spectrum profile for MM-grown samples showed major differences especially regarding the presence of anomeric signals attributed to α-D-Man p units, at δ 101.1/5.22 (Figures 2A,C) (Barreto-Bergter et al, 2008). On CD medium, the differentiation of the strains were related to α-D-Man p (1→6) and β-D-Man p (1→2) (Figures 2B,D), (Viccini et al, 2009). …”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…Examination of the 2D NMR spectrum profile for MM-grown samples showed major differences especially regarding the presence of anomeric signals attributed to α-D-Man p units, at δ 101.1/5.22 (Figures 2A,C) (Barreto-Bergter et al, 2008). On CD medium, the differentiation of the strains were related to α-D-Man p (1→6) and β-D-Man p (1→2) (Figures 2B,D), (Viccini et al, 2009). …”
Section: Resultsmentioning
confidence: 88%
“…The main difference found for this strain when comparing growth condition is the presence of signals corresponding to β-D-Gal f units (δ 106.0/5.23 and δ 105.3/5.23), on CD medium, in contrast to the signals attributed to α-D-Man p (δ 99.1/5.11) and β-D-Man p (δ 99.1/4.82 and 101.3/5.11) (Viccini et al, 2009) found for the MM samples (Figures 2A,B). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1D and 2D assignments were performed using 1 H-(zg, and zgpr) and HSQC (hsqcetgpsi) programs. HSQC was acquired using 8-16 scans, respectively, per series of 2 K × 512 W data points with zero filling in F1 (4 K) prior to Fourier transformation (Viccini et al, 2009). …”
Section: Nuclear Magnetic Resonance (Nmr)mentioning
confidence: 99%